The Social Brain and the Shape of the Palaeolithic - Gamble, C; Gowlett, J; Dunbar, R; Project, B (2011)
It is often the case in interdisciplinary accounts of human evolution that archaeological data are either ignored or treated superficially. This article sets out to redress this position by using archaeological evidence from the last 2.5 million years to test the social brain hypothesis (SBH) - that our social lives drove encephalization. To do this we construct a map of our evolving social complexity that concentrates on two resources - materials and emotions - that lie at the basis of all social interaction. In particular, novel cultural and biological mechanisms are seen as evolutionary responses to problems of cognitive load arising from the need to integrate more individuals and sub-units into the larger communities predicted by the SBH. The Palaeolithic evidence for the amplification of these twin resources into novel social forms is then evaluated. Here the SBH is used to differentiate three temporal movements (2.6-1.6 Ma, 1.5-0.4 Ma and 300-25 ka) and their varied evolutionary responses are described in detail. Attention is drawn to the second movement where there is an apparent disconnect between a rise in encephalization and a stasis in material culture. This disconnect is used to discuss the co-evolutionary relationship that existed between materials and emotions to solve cognitive problems but which, at different times, amplified one resource rather than the other. We conclude that the shape of the Palaeolithic is best conceived as a gradient of change rather than a set of step-like revolutions in society and culture. Copyright © The McDonald Institute for Archaeological Research 2011.